Peran Guru Pendidikan Agama Kristen Dalam Mengembangkan Kepedulian Ekologi Pada Generasi Muda Kristen - Biaf, Raymon Imanuel; Tari, Ezra (P3M POLITEKNIK NEGERI AMBON, 2024)
the increasingly alarming ecological crisis demands efforts to build awareness and concern for the environment, especially among the younger generation of Christians. This study aims to determine the role of Christian Religious Education teachers in shaping a generation of Christians who care about the ecological crisis. Using a qualitative approach with descriptive methods, data collection was conducted through interviews, observations, and filling out questionnaires. The results showed that Christian Religious Education teachers have an important role in shaping a Christian generation that cares about the ecological crisis, which is realized through (a) Integration of ecological material in Christian Religious Education learning, such as the concept of creation, stewardship, and human responsibility towards nature (b) Exemplary teachers in behaving environmentally friendly and educating students to care about the environment (c) Development of environmental awareness-based activities and cleaning activities in the school environment and its surroundings. This study suggests that Christian Religious Education teachers should consistently integrate ecological issues in learning and provide examples of environmentally friendly behavior, as well as develop extracurricular programs that can foster environmental awareness in the Christian generation. The findings of this study confirm the significant contribution of Christian Religious Education teachers in developing ecological awareness in the younger generation of Christians. Keywords: Christian Religious Education Teacher; Christian Generation; Ecology